AuNPs / MXene nanomaterial-based aptamer electrochemical biosensor as well as preparation method and application thereof

AuNPs/MXene composites were prepared by growing AuNPs on the MXene surface, and combined with aptamer probes, a sensor suitable for chronic wound management was developed, which achieved rapid, sensitive and specific detection of TGF-β1, and solved the problem of The lack of real-time monitoring in the prior art.

CN119438576APending Publication Date: 2025-02-14CHONGQING MEDICAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411590727.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The lack of real-time, non-invasive monitoring methods in chronic wound management results in treatment lag and delayed healing.

Method used

Using an aptamer electrochemical biosensor based on AuNPs/MXene nanomaterials, AuNPs/MXene composite material was prepared by growing AuNPs on the surface of MXene, and fixed it on the electrode surface, and TGF-β1 was performed by combining the aptamer probe. Test.

Benefits of technology

Fast, sensitive and specific detection of TGF-β1 is achieved, with a wide detection range (1pg/ml~5ng/ml) and a low quantitative line (748fg/ml), suitable for in-situ detection of inflammatory factors at wounds .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005125515680000011
    Figure HDA0005125515680000011
  • Figure HDA0005125515680000012
    Figure HDA0005125515680000012
Patent Text Reader

Abstract

The invention discloses an aptamer electrochemical biosensor based on an AuNPs / MXene nanometer material and a preparation method and application of the aptamer electrochemical biosensor. According to the electrochemical biosensor, AuNPs particles grow on the surface of MXene, an AuNPs / MXene composite material is prepared, then the composite material is fixed to the surface of an electrode through chitosan, aptamer probes P1 and P2 are hybridized with MCH, and then the aptamer probes P1 and P2 are self-assembled to the surface of the electrode through Au-S bonds. According to the invention, the AuNPs / MXene nano material is prepared, and the AuNPs / MXene nano material and the AuNPs / MXene nano material play a synergistic effect, so that the performance of the sensor is further improved, the sensor has a wide detection range and a low quantitative line, and rapid, sensitive and specific detection on a sample can be realized. The sensor can be used for in-situ detection of inflammatory factors at a wound, can be applied to non-invasive instant wound nursing monitoring equipment, and provides reliable and timely monitoring data to realize more effective diagnosis and treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of immunoelectrochemical biosensors, and in particular to an aptamer electrochemical biosensor based on AuNPs / MXene nanomaterials, and a preparation method and application thereof. Background Art

[0002] Chronic wounds refer to wounds that fail to heal naturally due to multiple factors. They cannot recover to their normal anatomical structure and complete functions, and are usually accompanied by persistent inflammatory responses, cell migration disorders, and tissue remodeling problems. Currently, chronic non-healing wounds are an increasingly serious social problem. Chronic wound patients account for about 1-2% of the total population, and their treatment and care expenses account for 2-4% of total healthcare expenses. Due to problems such as diabetes, obesity, and an aging population, not only do they impose a heavy burden on patients' families, but they also put tremendous pressure on the healthcare system. Therefore, it is very necessary to manage chronic wounds.

[0003] Transforming growth factor beta 1 (TGF-β1) plays multiple regulatory roles in the wound healing process, including regulating inflammatory response, promoting fibroblast migration, stimulating extracellular matrix production, and participating in the formation of scar tissue. The level of TGF-β1 and its regulatory imbalance are often closely related to the healing disorder of chronic wounds. Therefore, real-time monitoring of TGF-β1 levels can provide an important basis for evaluating the healing status of chronic wounds and formulating personalized treatment strategies.

[0004] With the development of biosensor technology, wearable sensors have become a powerful tool for detecting chronic wounds, and screen-printed electrodes provide important support for the development of such sensors. By fixing recognition molecules (antibodies, enzymes, aptamers) on the surface of screen-printed electrodes and combining them with electrochemistry, accurate detection of biomarkers can be achieved. Screen-printed electrodes are made of flexible substrate materials, making them suitable for integration into wearable devices and attachment to human skin or wound surfaces. In addition, screen-printed electrodes are simple to make and low in cost, making them widely used in daily chronic wound management.

[0005] In biosensor applications, the introduction of nanomaterials has significantly improved the detection performance of sensors. MXene is a two-dimensional transition metal carbide, nitride or carbonitride. The typical chemical formula of the new two-dimensional nanomaterial MXene obtained by etching the layered material MAX phase to remove the A element is M n+1 X n T xWhere M represents a transition metal element (Ti, Sc, V, Cr, Zr, Nb, Mo, etc.), X represents C or N, and Tx is a variety of functional groups on the surface of MXene (-OH, -O, -F, etc.). MXene has excellent electrical conductivity and extremely high specific surface area due to its two-dimensional layered structure, which is conducive to the transfer of electrons and the progress of reactions. In addition, the various functional groups on its surface facilitate chemical modification and functionalization, and can enhance the ability to bind to external molecules. MAX phase is a ternary layered ceramic material, in which M is a transition metal element, A is mainly a third main group and a fourth main group element, and X is carbon or nitrogen. The crystal unit arrangement of this material is a hexagonal structure, and the space point group is P63 / mmc, in which the M atomic layer and the A atomic layer are arranged alternately to form a layered structure similar to a close-packed hexagonal structure, and the X atoms are filled in the gaps of the octahedron. Where M is a pre-transition metal element, A is a main group element, X is a carbon or nitrogen element, and n=1, 2, 3, so it is referred to as MAX phase. When n=1, it is 211 phase, such as Ti2AlC, Ti2SiC; when n=2, it is 312 phase, such as Ti3SiC2 and Ti3AlC2; when n=3, it is 413 phase, such as Ti4AlN3. MAX phase synthesis is mainly prepared by ball milling and mixing the raw material powder and then sintering it at high temperature. Gold nanoparticles (AuNPs) are a kind of nanomaterial with good electrical conductivity and high specific surface area. They have good biocompatibility and can react with many biological molecules without affecting their own properties.

[0006] At present, there are two main aspects of clinical management of chronic wounds. One is to evaluate the wound area, granulation tissue formation, epithelial regeneration and other characteristics with the naked eye for qualitative analysis. The second is to use laboratory detection methods to quantitatively analyze the biochemical parameters of the wound site, such as enzyme-linked immunosorbent assay. The main disadvantages are as follows: 1. Qualitative analysis of wounds by the naked eye has the disadvantage of relying on subjective judgment and lack of real-time monitoring of the wound environment, which often leads to lagging care and delayed healing of chronic wounds. 2. Laboratory methods for wound microenvironment detection are complex, expensive, time-consuming, and require professional operation, which is not convenient for daily wound management. 3. The wound healing process is complex and involves many biochemical parameters, and TGF-β1, which plays an important role in wound healing, is rarely detected. Summary of the invention

[0007] The purpose of the present invention is to address the above problems and provide an aptamer electrochemical biosensor based on AuNPs / MXene nanomaterials and a preparation method and application thereof.

[0008] In order to achieve its purpose, the present invention adopts the following technical solution:

[0009] The first aspect of the present invention provides a method for preparing an aptamer electrochemical biosensor based on AuNPs / MXene nanomaterials, which comprises growing AuNPs particles on the surface of MXene to prepare an AuNPs / MXene composite material, and then fixing the composite material on the electrode surface by chitosan, and after hybridization of aptamer probes P1 and P2 with MCH, self-assembling on the electrode surface through Au-S bonds, comprising the following steps:

[0010] S1. Preparation of AuNPs / MXene composite material: adding HAuCl4 to MXene aqueous dispersion, ultrasonically treating until fully mixed, centrifuging, washing, and freeze-drying to obtain AuNPs / MXene composite material powder; dispersing AuNPs / MXene powder in chitosan solution to obtain AuNPs / MXene chitosan solution for later use; the MXene is Ti3C2;

[0011] S2, electrode pretreatment: activating the electrode. After the electrode activation is completed, the AuNPs / MXene chitosan solution is coated on the working electrode area, incubated, and dried;

[0012] S3. Electrode functionalization: Probe P1 in the double-stranded DNA probe is mixed with a reducing agent in a buffer solution, incubated, and heated to promote the reducing agent to reduce the disulfide bonds in P1 (because the 5' end of P1 is modified with a thiol group, disulfide bonds will be formed between each other), and then cooled to room temperature before adding probe P2 and MCH to make the final concentrations of probe P1, reducing agent, probe P2 and MCH 0.1-5 μM, 5-250 μM, 0.1-5 μM, and 0.9-45 μM, and incubate to obtain a probe mixed solution; the probe mixed solution is dripped onto the pretreated electrode surface and incubated to obtain; the reducing agent is TCEP, DTT (dithiothreitol) or DTE (dithioerythritol), and the buffer is TE buffer or PBS buffer.

[0013] In step S1, MXene powder is added to deionized water to prepare a dispersion of 1.5-2.5 mg / ml, and mixed with 5 mM HAuCl4 solution at a volume ratio of 1.5-2.5:1, ultrasonically treated for 35-55 min, centrifuged, washed with deionized water, and freeze-dried to obtain AuNPs / MXene composite materials.

[0014] In the step S1, AuNPs / MXene powder is dispersed in a 0.3-0.7wt% or 0.4-0.6wt% chitosan solution to obtain an AuNPs / MXene chitosan solution with a concentration of 0.5-2mg / ml for standby use; preferably, the concentration of the AuNPs / MXene chitosan solution is 1-2mg / ml or 1-1.5mg / ml.

[0015] In step S2, after the electrode activation is completed, 7-16 μL or 10-13 μL AuNPs / MXene chitosan solution is added to the working electrode area, incubated in a dark room at 4-10°C for 8-16 hours, and dried; the electrode is a gold electrode or a glassy carbon electrode, preferably a screen-printed gold electrode.

[0016] In step S3, the probe P1 and the reducing agent TCEP are mixed in a buffer solution, incubated in a dark room at room temperature for 50 to 80 minutes, heated in a water bath at 50 to 60°C for 3 to 7 minutes, and then cooled to room temperature before adding probe P2 and MCH to make the final concentrations of probe P1, TCEP, probe P2 and MCH 0.5 to 5 μM, 2.5 to 250 μM, 0.5 to 5 μM, 4.5 to 45 μM or 1 to 2 μM, 40 to 100 μM, 1 to 2 μM, 8 to 18 μM or 1 μM, 50 μM, 1 μM, 9 μM, and incubated at room temperature for 8 to 12 minutes to obtain a probe solution, and the probe solution is dripped onto the pretreated electrode surface, and incubated in a dark room at 4 to 10°C overnight.

[0017] The preparation method of MXene comprises: using LiF / HCl etching solution to heat and stir etch MAX-Ti3AlC2, centrifuging, washing, ultrasonic stripping in a cold water bath, and freeze drying to obtain MXene powder.

[0018] A second aspect of the present invention provides an aptamer electrochemical biosensor based on AuNPs / MXene nanomaterials, which is prepared by any of the preparation methods described above.

[0019] The third aspect of the present invention provides the application of the above-mentioned aptamer electrochemical biosensor based on AuNPs / MXene nanomaterials in detecting proteins. The sensor is subjected to a chronoamperometry test in PBS to record the background current, and then the chronoamperometry test is performed again in PBS containing the protein to be tested. The current difference between the two at a fixed time point is calculated to achieve detection of the target object.

[0020] The application comprises the following steps:

[0021] 1) Establishing the standard curve equation: dripping PBS solution onto the electrode surface, allowing it to react fully at room temperature, and measuring the background current using the chronoamperometry method; then preparing standard solutions of the test object with different concentration gradients, dripping them onto the electrode surface, allowing it to react fully at room temperature, and measuring the response current using the chronoamperometry method; and calculating the current difference between the two at a fixed time; establishing the standard curve equation based on the relationship between the concentration of the test object in the standard solution and the current signal;

[0022] 2) Measuring the response current: dripping PBS solution or artificial body fluid onto the electrode surface, allowing it to react fully at room temperature, and measuring the background current using the chronoamperometry. Then dripping the sample solution onto the electrode surface, allowing it to react fully at room temperature, and measuring the response current using the chronoamperometry. Calculate the current difference between the two at a fixed time.

[0023] 3) Substituting the current difference signal obtained in step 2) into the standard curve equation in step 1) to calculate the concentration of the target detection object in the sample solution to be tested.

[0024] The application, wherein the object to be tested is TGF-β1;

[0025] The sequence of probe P1 is: 5′-SH-C6-TACCAGCTATTGTATCTAATAAGA-MB-3′;

[0026] The sequence of probe P2 is:

[0027] 5′-CG*CTCGG*CTTC*ACG*AG*ATT*CGTGT*CGTTGTGT*C*CTGT*A*C*C*CG*C*CTTG*A*C*C*AGT*C*ACT*CT*AG*AGC*AT*C*CGG*A*CTGTTTTCTTATTAGATACA ATAGCTGGTA-3′, where * represents phosphorothioate modification;

[0028] The concentration of the TGF-β1 standard solution in step 1) is 0.5pg / ml to 7ng / ml, preferably 1pg / ml to 5ng / ml, and the preferred different concentrations of the TGF-β1 standard solution are 1pg / ml, 10pg / ml, 100pg / ml, 1ng / ml, and 5ng / ml.

[0029] The beneficial effects of the present invention are:

[0030] By growing AuNPs on the surface of MXene and preparing AuNPs / MXene nanomaterials, the two can play a synergistic role and further improve the material performance. Since the AuNPs / MXene composite material has excellent electrical conductivity and a large specific surface area, it can reduce the loss during electron transmission and provide more fixed points for the probe. Therefore, the sensor of the present invention has excellent performance as a whole, with a wide detection range (1pg / ml~5ng / ml) and a low quantitative line (748fg / ml), which can achieve rapid, sensitive and specific detection of samples. It has low preparation cost, portability, good stability and repeatability, and has good market application prospects.

[0031] The application of the sensor of the present invention is based on a new detection principle, based on the principle of analyte-induced aptamer conformational conversion, using rigid double-stranded DNA as a molecular pendulum, fixing the recognition chain and methylene blue (MB) at the top of the double-stranded DNA rod for target identification and signal detection, applying a constant step voltage by chronoamperometry to attract the aptamer probe modified with methylene blue to fall to the electrode surface in a motion similar to an inverted pendulum, and collecting the change of the current signal by chronoamperometry before and after the analysis probe binds to the target (such as TGF-β1) (the probe that does not bind to the target falls faster, and the current decays faster; the probe that binds to the target falls slower, and the current decays slower), and the quantitative analysis is realized by calculating the current difference of the fixed sampling time. This method is different from the detection principle of most aptamer sensors on the market, fixing the electrical signal substance at a low position, can overcome the shielding effect brought by the Debye effect, is more conducive to electronic transmission, and makes the sensor show a lower quantitative line. This method can be used for the detection of different substances, and can also have a good performance for substances with lower detection requirements, so it has a good application value.

[0032] The sensor of the present invention can be used for in situ detection of inflammatory factors at the wound site, and can be applied as a non-invasive instant wound care monitoring device to provide reliable and timely monitoring data to achieve more effective diagnosis and treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a scanning electron microscope image of MXene.

[0034] Figure 2 This is the scanning electron microscope image of AuNPs / MXene.

[0035] Figure 3 are the X-ray diffraction patterns of MAX, MXene and AuNPs / MXene.

[0036] Figure 4 This is the energy spectrum analysis diagram of AuNPs / MXene.

[0037] Figure 5 This is the particle size analysis electron microscope image of AuNPs / MXene.

[0038] Figure 6 It is a bar chart of the particle size distribution of AuNPs / MXene.

[0039] Figure 7 It is a cyclic voltammetry characterization test of the sensor.

[0040] Figure 8 It is the electrochemical impedance characterization of the sensor.

[0041] Fig. 9is the probe density measurement.

[0042] Fig.10 This is the experimental result of the optimal application volume of AuNPs / MXene.

[0043] Fig.11 This is the experimental result of the optimal concentration of AuNPs / MXene.

[0044] Fig.12 These are the experimental results comparing different protein incubation times.

[0045] Fig.13 This is the result of a comparative experiment of different Apt concentrations.

[0046] Fig.14 This is the detection principle of the sensor of the present invention.

[0047] Fig.15 is a qualitative response to gradient concentration.

[0048] Fig.16 It is the result of the gradient concentration quantitative response experiment.

[0049] Fig.17 Concentration response functions (compared to bare electrode) are shown.

[0050] Fig.18 Concentration qualitative responses (compared to bare electrode) are shown.

[0051] Fig.19 It is the experimental result of sensor stability (compared with bare electrode).

[0052] Fig. 20 is the sensor specificity experimental result.

[0053] Fig.21 It is the result of sensor regeneration and reuse experiment.

[0054] Fig. 22 It is the experimental result of simulating actual application of the sensor in artificial body fluid. DETAILED DESCRIPTION

[0055] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited thereto.

[0056] The experimental methods in the following examples are conventional methods unless otherwise specified.

[0057] Main materials / sources:

[0058] Titanium aluminum carbide (Ti3AlC2) MAX phase ceramic material: referred to as MAX-Ti3AlC2 powder (CAS No.: 196506-01-1), purchased from Xianfeng Nanomaterial Technology Co., Ltd. (China);

[0059] LiF: lithium fluoride, commercially available;

[0060] HAuCl4: tetrachloroauric acid, commercially available;

[0061] TCEP: tris(2-carboxyethyl)phosphine, CAS registration number 5961-85-3, commercially available;

[0062] MCH: 6-mercapto-1-hexanol, CAS registration number 1633-78-9, commercially available;

[0063] Apt probes include probes P1 and P2:

[0064] The sequence of probe P1 is (SEQ ID NO. 1): 5′-SH-C6-TACCAGCTATTGTATCTAATAAGA-MB-3′;

[0065] The sequence of probe P2 is (SEQ ID NO. 2): 5′-CG*CTCGG*CTTC*ACG*AG*ATT*CGTG T*CGTTGTGT*C*CTGT*A*C*C*CG*C*CTTG*A*C*C*AGT*C*ACT*CT*AG*AGC*AT*C*CGG*A*CTGTTTTCTTATTAGATACAATAGCTGGTA-3′ (where * indicates a phosphorothioate modification at that position).

[0066] In the aptamer probe, in order to detect a certain protein, the base sequence of P2 from the lower end (5' end) upwards is designed to be a sequence that can perform base complementary pairing with P1, and the base sequence from the upper end (3' end) downwards is designed to be a sequence that can bind to the target; after P1 and P2 are combined, they become a double-stranded DNA (dsDNA) probe.

[0067] Example 1

[0068] 1. Sensor production

[0069] MXene reduces HAuCl4 to grow AuNPs particles on the MXene surface to prepare AuNPs / MXene composite materials, which are then fixed on the electrode surface by chitosan. After the aptamer probes P1, P2 and MCH are hybridized, they are self-assembled on the electrode surface through Au-S bonds, and finally the response signal is measured by chronoamperometry (CA). The sensor production includes the following steps:

[0070] (1) Preparation of MXene: 40 ml of HCl (9M) solution was poured into a polytetrafluoroethylene beaker, and 0.8 g of LiF powder was weighed and poured into the beaker. The HCl / LiF etching solution was obtained by covering the beaker and stirring at room temperature for 20 min. 0.5 g of MAX-Ti3AlC2 powder was weighed and slowly poured into the beaker in batches to prevent the powder from releasing a large amount of solution when it is not mixed with the system and causing the reaction system to boil. After all the powder was poured in, a plastic wrap with small holes was covered on the mouth of the cup to seal the reaction system so that the hydrogen gas of the reaction could be discharged. The system temperature was set to 35 °C and stirred continuously (400 rpm, 24 h). After the reaction was completed, the mixed solution was transferred to a centrifuge tube and washed several times with deionized water by centrifugation (4000 rpm, 5 min) until the pH of the upper liquid was >6. Before that, all the upper liquid was discarded. After the pH of the upper liquid was >6, the upper liquid of the last centrifugation was discarded, deionized water was added again to shake well, and then poured into a silk-mouth bottle and ultrasonicated in an ice bath for 1 h. After the ultrasound is finished, the solution is centrifuged continuously, and the upper liquid is retained by centrifugation. The upper liquid is freeze-dried for 48 hours to obtain MXene powder (i.e., Ti3C2). Titanium carbide (Ti3C2) MXene nanomaterials can also be directly purchased commercially.

[0071] (2) Preparation of AuNPs / MXene: The MXene powder obtained in step (1) was added to deionized water to prepare a 2 mg / ml dispersion, and mixed with HAuCl4 (5 mM) solution at a volume ratio of 2:1. The mixture was ultrasonically treated for 45 min, centrifuged, washed with deionized water 5 times, and freeze-dried for 48 h to obtain an AuNPs / MXene composite material. Finally, the AuNPs / MXene was dispersed in a chitosan solution (0.5%, wt%) to obtain an AuNPs / MXene chitosan solution for subsequent experiments.

[0072] (3) Electrode pretreatment: The surface of the screen-printed gold electrode was rinsed with deionized water and anhydrous ethanol in turn. After drying with nitrogen, cyclic voltammetry was performed in H2SO4 (0.5 M) to activate the gold electrode surface. After the electrode activation was completed, 10 μL of AuNPs / MXene chitosan solution (2 mg / ml) was added to the working electrode area, incubated in a dark room at 4°C for 12 h, and then dried.

[0073] (4) Electrode functionalization: Probe P1 (20 μM) and TCEP (1 mM) were mixed in TE buffer, incubated at room temperature in the dark for 1 h, heated in a 55°C water bath for 5 min, cooled to room temperature, and then probe P2, MCH, and TE buffer were added to make the final concentrations of probe P1, TCEP, probe P2, and MCH 1 μM, 50 μM, 1 μM, and 9 μM, respectively. The prepared probe solution was obtained by incubating at room temperature for 10 min, and 10 μL of the probe solution was dripped onto the electrode surface. The solution was incubated at 4°C in the dark overnight. The sensor was stored in 0.1× PBS before the measurement experiment.

[0074] Figure 1 This is a scanning electron microscope image of MXene, where an obvious accordion multilayer structure is observed, indicating that the LiF / HCl etchant successfully etches MAX-Ti3AlC2, removes the Al layer, and leaves the MXene nanosheet intact without destroying its structure. The above experimental phenomena indicate that MXene nanomaterials have been successfully prepared.

[0075] Figure 2 This is a scanning electron microscope image of AuNPs / MXene. Many AuNPs of uniform size can be observed on the surface of MXene, which are evenly distributed on the surface of MXene. Figure 5-6 The diameter distribution of AuNPs on its surface was analyzed and the result was 13.71±2.2nm. Within this diameter range, AuNPs showed good conductive properties and high specific surface area. Figure 3 Figure 2 shows the X-ray diffraction patterns of MAX, MXene and AuNPs / MXene. After LiF / HCl etching, the Al in Ti3AlC2 is significantly reduced, the (002) peak shifts to the left (green dotted line), and the interplanar spacing increases. After AuNPs are fixed on the MXene surface, the characteristic peaks of Au (111)(200)(220)(331) appear. Figure 4 The energy spectrum analysis diagram of AuNPs / MXene shows that the prepared material is composed of Au, C, Cl, F, O and Ti. The content of components is as follows Figure 4 As described in the table. Based on the above experimental phenomena, it is shown that AuNPs / MXene nanomaterials were successfully prepared.

[0076] 2. Sensor Characterization Test

[0077] Corresponding characterization tests are performed for each step in the sensor manufacturing process.

[0078] Figure 7 and Figure 8 For the characterization of the sensor assembly steps by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS), the working solution was 5 mM [Fe(CN)6] 3- / 4- and 0.1 M KCl (1x PBS), CV potential interval -0.4 V-0.6 V, scan rate 0.1 V / s, EIS frequency range 10 -1 -10 -5 , amplitude 0.05mV. When AuNPs / MXene is fixed on the electrode surface (green), compared with the bare electrode (purple), the electrode conductivity is improved, the peak current increases, and the impedance decreases; after the Apt probe and MCH are fixed on the electrode surface, the impedance increases and the peak current decreases. When Apt and tgf-β1 are combined (yellow), the protein hinders electron transport, the peak current further decreases and the impedance increases. Fig. 9 In order to characterize the Apt probe density on the electrode surface by the chronocoulometry, the Apt probe density was calculated by measuring the difference in charge before and after adsorption based on the principle of electrostatic adsorption of RuHex by the DNA phosphate backbone. The probe density was calculated to be 3.0684×10 19 ±0.05molecules / cm 2 The calculation formula is as follows:

[0079]

[0080] Γ DNA =Γ0(z / m)(N A )

[0081] In the formula,

[0082] Q: Total power

[0083] n: number of electron transfers in the electrode reaction

[0084] F: Faraday constant

[0085] A: Electrode area

[0086] D0: Diffusion coefficient

[0087] t: electrolysis time

[0088] C: Concentration of electroactive species

[0089] QD l : Charge capacity of the double layer

[0090] Γ0: The amount of redox marker confined near the electrode surface

[0091] Γ DNA :DNA probe density

[0092] m: number of bases in the DNA probe

[0093] z: charge of the redox molecule

[0094] N A : Avogadro's constant.

[0095] 3. Sensor performance optimization experiment

[0096] In order to explore the optimal performance production scheme for the sensor, a series of gradient concentration experiments were conducted on the AuNPs / MXene volume, AuNPs / MXene concentration, protein incubation time and Apt concentration in the sensor production process.

[0097] Fig.10To obtain the optimal volume of AuNPs / MXene, the modification effects of AuNPs / MXene with different volumes were measured and compared by CV. 4, 7, 10, 13, and 16 μL of AuNPs / MXene were used to prepare sensors. As the volume of the nanomaterials increased, the conductivity continued to increase, but signal suppression occurred after exceeding 10 μL. This may be due to signal suppression caused by excessive addition of nanomaterials. Therefore, 10 μL is the optimal volume.

[0098] Fig.11 The optimal concentration of AuNPs / MXene was obtained. The modification effects of AuNPs / MXene at different concentrations were measured and compared by CV. 0.5, 1, 1.5, 2 and 3 mg / ml of AuNPs / MXene were used to prepare sensors. As the concentration of nanomaterials increased, the conductivity continued to increase, but signal suppression occurred after exceeding 1 mg / ml. This may be due to signal suppression caused by excessive addition of nanomaterials. Therefore, 1 mg / ml is the optimal concentration.

[0099] Fig.12 The optimal incubation time for the protein was 50 min. The protein incubation time (10, 20, 30, 40, 50, 60, 70, and 80 min) was measured and compared by CA. The incubation time showed an upward trend in the first 50 min. When the incubation time reached 50 min, the signal reached the maximum and was stable. Therefore, 50 min was the optimal incubation time for the protein.

[0100] Fig.13 To obtain the optimal concentration of Apt, the detection signals after modification with different concentrations of Apt were measured and compared by CA, and 0.1, 0.5, 1, 2, and 3 μM Apt were selected to prepare the sensor. As the Apt concentration continued to increase, the detection signal continued to rise until it reached a maximum at 1 μM, followed by signal inhibition.

[0101] 4. Sensor Detection

[0102] (1) Detection principle: Based on the principle of analyte-induced aptamer conformational transition, a molecular pendulum recognition element is constructed to analyze the kinetic information when the target is present or not.

[0103] (2) Detection process: The sensor was first tested by chronoamperometry in 0.1× PBS to record the background current, and then the sensor was tested by chronoamperometry again in 0.1× PBS containing TGF-β1, and the current difference between the two at fixed time points was calculated.

[0104] The specific steps are as follows:

[0105] 1) Establishing the standard curve equation: adding 0.1×PBS solution to the electrode surface, allowing it to react fully at room temperature, and measuring the background current by chronoamperometry. Then, preparing standard solutions of TGF-β1 with different concentration gradients, adding them to the electrode surface, allowing it to react fully at room temperature, and measuring the response current by chronoamperometry. Calculate the current difference between the two at a fixed time. Establishing the standard curve equation based on the relationship between the concentration of TGF-β1 in the standard solution and the current signal. The different concentrations of the TGF-β1 standard solution are 1pg / ml, 10pg / ml, 100pg / ml, 1ng / ml, and 5ng / ml.

[0106] 2) Measure the response current: add 0.1×PBS solution to the electrode surface, allow it to react fully at room temperature, and use the chronoamperometry to measure the background current. Then add the sample solution to the electrode surface, allow it to react fully at room temperature, and use the chronoamperometry to measure the response current. Calculate the current difference between the two at a fixed time.

[0107] 3) Substituting the current difference signal obtained in step 2) into the standard curve equation in step 1) to calculate the concentration of TGF-β1 in the sample solution to be tested.

[0108] (3) Sensor performance testing: The sensor is tested in various aspects, including concentration response, stability, repeatability and specificity.

[0109] Fig.14 Based on the sensor detection principle, a constant step voltage is applied to the molecular pendulum through CA to attract the far end of the molecular pendulum close to the electrode surface to generate current. The current is initially at its maximum value and gradually decays over time. Since the current decay characteristics τ of the molecular pendulum model before and after binding to the protein are different, the response current is calculated by sampling the current value at a fixed time to achieve quantitative analysis of the target.

[0110] Fig.15 It is a qualitative response to gradient concentration. The measured concentrations are 1ng / ml, 100pg / ml and 10pg / ml. Compared with the control group, they all show current signal responses of distinguishable sizes. The size of the current signal increases with the increase of concentration.

[0111] Fig.16 It is a gradient concentration quantitative response, and the measured concentrations are 5ng / ml, 3ng / ml, 1ng / ml, 100pg / ml, 50pg / ml, 10pg / ml, and 1pg / ml. The results show that the current response signal increases with the increase of TGF-β1 concentration, and can show distinguishable signal changes even at a concentration as low as 1pg / ml. Each group of response current values ​​is subjected to a two-sample t-test, and the results all show p<0.001, so the results are statistically significant.

[0112] Fig.17 is the concentration response function, where the black one is the sensor designed in this study, and the red one is the sensor of unmodified AuNPs / MXene nanomaterials. The basic electrodes of the two are the same. The results show that the sensor modified with AuNPs / MXene shows significantly better sensitivity and detection range than the bare electrode, with a linear range of 1pg / ml to 5ng / ml, and the standard curve regression equation is y=13.63lgC+13.14. The limit of quantification is as low as 748fg / ml, and the concentration gradient response linearity is good, r 2 =0.98. The linear range of the sensor for unmodified AuNPs / MXene nanomaterials is only 100pg / ml to 5ng / ml, and the standard curve regression equation is y=3.42lgC+3.35, r 2 =0.97, limit of quantification 7.89pg / ml.

[0113] Fig.18 For the concentration qualitative response control experiment, the measured concentration was 100pg / ml. Both produced distinguishable current response signals. The response signal ΔI2 produced by the bare electrode was significantly lower than the response signal ΔI1 produced by the AuNPs / MXene modified electrode. The above experimental results show that the detection method proposed in this study can be used for actual detection, and the nanomaterial modification scheme adopted can improve the sensor detection performance.

[0114] Fig.19 For the sensor stability control experiment, two production schemes were adopted for the same batch of sensors, and their stability was tested within 15 days, including measurement experiments on days 3, 5, 7, 9, 11, 13, and 15 respectively. The final experimental results showed that the sensors modified with AuNPs / MXene showed better stability. The sensor detection signal could maintain a signal strength of about 82% on the 15th day, while the bare electrode only maintained a signal strength of about 65%.

[0115] Fig. 20 For sensor specificity testing, several common components in wound exudate, including interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and vascular endothelial growth factor (VEGF), were selected. These substances were prepared into test solutions of the same concentration using 0.1x PBS for detection. The results showed that the sensors for IL-6, TNF-α and VEGF exhibited lower response currents and were difficult to distinguish from the blank group, while the detection of TGF-β1 showed an obvious current response.

[0116] Fig.21For regeneration and reuse performance testing, a batch of sensors were tested for TGF-β1, and then the electrode surface was rinsed with 0.1xPBS, and then the detection experiment (1ng / ml) was repeated 5 times. The results showed that the response signal decreased with the increase of elution times, and the background current increased with the increase of elution times. At the fifth detection, the response signal was 77% of the initial response signal, so the sensor can be used for continuous detection of TGF-β1.

[0117] Fig. 22 To carry out detection in artificial body fluid (Simulated Body Fluid, SBF) (Solarbio; Product Number: G0390), the solvent of the experimental group was artificial body fluid, and the solvent of the control group was 0.1x PBS. The detection concentrations were 1ng / ml, 100pg / ml, 50pg / ml, 10pg / ml and 1pg / ml. The experimental results showed that there was no significant difference in the current response signal in artificial body fluid and that in 0.1x PBS. Therefore, the sensor can be used for actual detection of wound exudate.

[0118] In summary, the sensor showed good specificity and was able to specifically detect TGF-β1.

Claims

1. A method for preparing an aptamer electrochemical biosensor based on AuNPs / MXene nanomaterials, characterized in that: The method is to grow AuNPs particles on the surface of MXene to prepare AuNPs / MXene composite materials, and then fix the composite materials on the electrode surface through chitosan. After the aptamer probes P1, P2 and MCH are hybridized, they are self-assembled on the electrode surface through Au-S bonds, including the following steps: S1. Preparation of AuNPs / MXene composite material: adding HAuCl4 to MXene aqueous dispersion, ultrasonically treating until fully mixed, centrifuging, washing, and freeze-drying to obtain AuNPs / MXene composite material powder; dispersing AuNPs / MXene powder in chitosan solution to obtain AuNPs / MXene chitosan solution for later use; the MXene is Ti3C2; S2, electrode pretreatment: activating the electrode. After the electrode activation is completed, the AuNPs / MXene chitosan solution is coated on the working electrode area, incubated, and dried; S3. Electrode functionalization: Mix the probe P1 in the double-stranded DNA probe with the reducing agent in a buffer solution, incubate them, heat to promote the reducing agent to reduce the disulfide bonds in P1, let them cool to room temperature, then add probe P2 and MCH to make the final concentrations of probe P1, reducing agent, probe P2 and MCH 0.1-5 μM, 5-250 μM, 0.1-5 μM, 0.9-45 μM, and incubate to obtain a probe mixed solution; drop the probe mixed solution on the pretreated electrode surface, incubate to obtain; the reducing agent is TCEP, DTT or DTE, and the buffer is TE buffer or PBS buffer.

2. The preparation method according to claim 1, characterized in that: In step S1, MXene powder is added to deionized water to prepare a dispersion of 1.5-2.5 mg / ml, and mixed with 5 mM HAuCl4 solution at a volume ratio of 1.5-2.5:1, ultrasonically treated for 35-55 min, centrifuged, washed with deionized water, and freeze-dried to obtain AuNPs / MXene composite materials.

3. The preparation method according to claim 1, characterized in that: In the step S1, AuNPs / MXene powder is dispersed in a 0.3-0.7wt% or 0.4-0.6wt% chitosan solution to obtain an AuNPs / MXene chitosan solution with a concentration of 0.5-2mg / ml for standby use; preferably, the concentration of the AuNPs / MXene chitosan solution is 1-2mg / ml or 1-1.5mg / ml.

4. The preparation method according to claim 3, characterized in that: In step S2, after the electrode activation is completed, 7-16 μL or 10-13 μL AuNPs / MXene chitosan solution is added to the working electrode area, incubated in a dark room at 4-10°C for 8-16 hours, and dried; the electrode is a gold electrode or a glassy carbon electrode, preferably a screen-printed gold electrode.

5. The preparation method according to claim 1, characterized in that: In step S3, the probe P1 and the reducing agent TCEP are mixed in a buffer solution, incubated in a dark room at room temperature for 50 to 80 minutes, heated in a water bath at 50 to 60°C for 3 to 7 minutes, and then cooled to room temperature before adding probe P2 and MCH to make the final concentrations of probe P1, TCEP, probe P2 and MCH 0.5 to 5 μM, 2.5 to 250 μM, 0.5 to 5 μM, 4.5 to 45 μM or 1 to 2 μM, 40 to 100 μM, 1 to 2 μM, 8 to 18 μM or 1 μM, 50 μM, 1 μM, 9 μM, and incubated at room temperature for 8 to 12 minutes to obtain a probe solution, and the probe solution is dripped onto the pretreated electrode surface, and incubated in a dark room at 4 to 10°C overnight.

6. The preparation method according to claim 1, characterized in that: The preparation method of the MXene is: MAX-Ti3AlC2 was etched by heating and stirring using LiF / HCl etching solution, centrifuged, washed, ultrasonically stripped in a cold water bath, and freeze-dried to obtain MXene powder.

7. An aptamer electrochemical biosensor based on AuNPs / MXene nanomaterials, characterized in that: The preparation method is described in any one of claims 1 to 6.

8. The use of the aptamer electrochemical biosensor based on AuNPs / MXene nanomaterials in detecting proteins according to claim 7, characterized in that: The sensor was tested by chronoamperometry in PBS to record the background current, and then the sensor was tested again by chronoamperometry in PBS containing the protein to be tested, and the current difference between the two at fixed time points was calculated to achieve detection of the target object.

9. The use according to claim 8, characterized in that: The application comprises the following steps: 1) Establish the standard curve equation: add PBS solution to the electrode surface, fully react at room temperature, measure the background current by chronoamperometry, then prepare standard solutions of the test object with different concentration gradients, add them to the electrode surface, fully react at room temperature, measure the response current by chronoamperometry, and calculate the current difference between the two at a fixed time; Establishing a standard curve equation based on the relationship between the concentration of the test object in the standard solution and the current signal; 2) Measuring the response current: dripping PBS solution or artificial body fluid onto the electrode surface, allowing it to react fully at room temperature, and measuring the background current using the chronoamperometry. Then dripping the sample solution onto the electrode surface, allowing it to react fully at room temperature, and measuring the response current using the chronoamperometry. Calculate the current difference between the two at a fixed time. 3) Substituting the current difference signal obtained in step 2) into the standard curve equation in step 1) to calculate the concentration of the target detection object in the sample solution to be tested.

10. The use according to claim 9, characterized in that: The object to be tested is TGF-β1; The sequence of probe P1 is: 5′-SH-C6-TACCAGCTATTGTATCTAATAAGA-MB-3′; The sequence of probe P2 is: 5′-CG*CTCGG*CTTC*ACG*AG*ATT*CGTGT*CGTTGTGT*C*CTGT*A*C*C*CG*C*CTTG*A*C*C*AGT*C*ACT*CT*AG*AGC*AT*C*CGG*A*CTGTTTTCTTATTAGATACA ATAGCTGGTA-3′, where * represents phosphorothioate modification; The concentration of the TGF-β1 standard solution in step 1) is 0.5pg / ml to 7ng / ml, preferably 1pg / ml to 5ng / ml, and the preferred different concentrations of the TGF-β1 standard solution are 1pg / ml, 10pg / ml, 100pg / ml, 1ng / ml, and 5ng / ml.

Citation Information

Cited By

  • Inverted TDN modified electrode, CRISPR / Cas12a mediated DNA tetrahedral reporter probe interface cleavage ratio type electrochemical aptamer sensor and application

    CN120275470A